ISOLATION, CHARACTERIZATION OF CELLULASE PRODUCING LYSINIBACILLUS SPHAERICUS MTCC NO. 9468 FROM GUT OF EISENIA FOETIDA - K. PAVANA JYOTSNA,; K. VIJAYALAKSHMI,; N. D. PRASANNA,; S. K. SHAHEEN, (The Bioscan, 2011)
Twenty bacteria were isolated from the gut of earthworm (Eisenia foetida). Cellulolytic enzyme activity of the cultures from the gut was screened on CMC (Carboxy Methyl Cellulose) medium. All the isolates were found positive for cellulase production. Among the twenty isolates, EGB1 isolate which showed maximum activity was categorized as Lysinibacillus sphaericus with MTCC No. 9468 (formerly Bacillus sphaericus) based on cultural, morphological, physiological and biochemical characteristics.